The impact of occupational health, safety, workload, and stress on nurses during the COVID-19 pandemic - Athira Rafida Hanum; M. Muhardi; Sri Suwarsi (Universitas Muhammadiyah Magelang, 2022)
The COVID-19 pandemic impacts the clinical nurses working in hospitals. The pandemic challenged them to deal with unfamiliar problems such as heavy workloads and adaptation to using Personal Protective Equipment (PPE). When left untreated, the situation will increase the stress among nurses. Due to this reason, the objective of the study is to evaluate the impact of pandemic health, safety, workload, and stress among nurses in a hospital. The study used descriptive design and used observational methods to reach the research objective. The data collection process was started from August 2020 to October 2020. A total of 144 nurses were engaged during the study. Several instruments were used to gain data from the participants. Regression analysis was used for hypothesis testing. The finding indicated that results of this study indicate that OHS, workload, and work stress simultaneously have a significant positive effect on the nurses’ performance (p < 0.05). This research suggests that health policymakers should provide psychological support for nurses experiencing stress when delivering care. Keywords: Occupational health; safety; nurses; psychological stress; pandemic